Effects of Feeding Finishing Pig Diets Differing in Ca:P Ratio, Added Phytase and Vitamin D Sources on Growth Performance, Weight Variation, Serum 25(OH)D3, Carcass Characteristics, Bone Characteristics, and Economics - Hilario M. Cordoba; Jason C. Woodworth; Robert D. Goodband; Joel M. DeRouchey; Mike D. Tokach; Jordan T. Gebhardt; Jon R. Bergstrom (Kansas Agricultural Experiment Station Research Reports, 2023)
A total of 2,160 grow-finish pigs (PIC 337 × 1050; initially 71.8 ± 1.4 lb) were used in a 114-d trial to determine the effects of feeding diets differing in Ca:P ratio and added phytase or phytase and 25(OH)D3(Hy-D, DSM Nutritional Products, Parsippany, NJ) on growth performance, weight variation, serum 25(OH)D3, bone characteristics, and economics. Pigs were housed in mixed gender pens with 27 pigs per pen and 20 pens per treatment. The four treatments were structured as a randomized complete block design and consisted of: 1) a high phosphorus (HP) diet formulated to a 1.25:1 Ca to P ratio with STTD P at 115% of NRC requirement estimate without inclusion of phytase; 2) low phosphorus (LP) diet initially formulated to a 1.25:1 Ca to P ratio with STTD P at 80% of NRC requirement without the addition of phytase; 3) HP with phytase (HP+phytase) diet with a 1.1:1 Ca to P ratio with STTD P at 115% of NRC requirement using 0.125% STTD P release from 600 FYT/kg HiPhorius; and 4) Same as diet 3 except 25(OH)D3replacing most of the vitamin D3in the diet (HP+25(OH)D3). Diets were fed in meal form with phase 1 fed from 71 to 110 lb, phase 2 from 110 to 165 lb, phase 3 from 165 to 220 lb, and phase 4 from 220 to 293 lb. Overall, source of vitamin D had no impact on performance, but pigs fed HP diets had improved (P<0.05) ADG, ADFI, and F/G compared to those fed LP diets, and ADFI was greater compared to those fed the HP+phytase diet with 1.1:1 Ca to P ratio. For serum 25(OH)D3measured on d 50, pigs fed the HP diets had increased (P<0.05) levels of 25(OH)D3compared to pigs fed the LP diets, and pigs fed the HP+25(OH)D3diets had increased (P<0.05) serum levels of 25(OH)D3compared to pigs fed the HP+phytase diets. Pigs fed the HP diets had greater (P<0.05) HCW and percentage lean than those fed LP diets. For economics results, pigs fed HP diets had increased (P<0.05) feed cost, revenue, and income over feed cost (IOFC) compared to those fed LP diets in both a low and high price scenario. For bone analysis, pigs fed HP diets, had greater (P<0.05) bone ash (g) and breaking strength than pigs fed LP or HP+phytase with a reduced Ca to P ratio. In conclusion, when pigs were fed 115% of NRC STTD P requirements, growth performance, HCW, and economics were improved compared to those fed at 80% of the P requirements.
Keywords: finishing pigs; calcium; 25-hydroxy-D3; body weight variation; carcass characteristics